2018
DOI: 10.3389/fmicb.2018.01352
|View full text |Cite
|
Sign up to set email alerts
|

Tunicamycin Mediated Inhibition of Wall Teichoic Acid Affects Staphylococcus aureus and Listeria monocytogenes Cell Morphology, Biofilm Formation and Virulence

Abstract: The emergence of bacterial resistance to therapeutic antibiotics limits options for treatment of common microbial diseases. Subinhibitory antibiotics dosing, often aid in the emergence of resistance, but its impact on pathogen’s physiology and pathogenesis is not well understood. Here we investigated the effect of tunicamycin, a cell wall teichoic acid (WTA) biosynthesis inhibiting antibiotic at the subinhibitory dosage on Staphylococcus aureus and Listeria monocytogenes physiology, antibiotic cross-resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 80 publications
1
52
0
Order By: Relevance
“…In addition to the collective protection to antimicrobials that can be provided by the extracellular matrix, our data suggest that individual cells might develop protection against external aggressors by enhancing the physical barrier represented by the cell wall. Besides, in B. subtilis , it has been reported the importance of transglycosylation and transpeptidation of the PG, as well as the wall teichoic acid for biofilm formation, which disturbance affect the cell wall structure and drastically affect the extracellular matrix anchoring [36, 37]. Lipoteichoic acid (LTA) is a major component of the cell wall in Gram-positive bacteria, and the LTA synthase ( BC3765 ) is upregulated in 48- and 72-hour aged biofilms.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the collective protection to antimicrobials that can be provided by the extracellular matrix, our data suggest that individual cells might develop protection against external aggressors by enhancing the physical barrier represented by the cell wall. Besides, in B. subtilis , it has been reported the importance of transglycosylation and transpeptidation of the PG, as well as the wall teichoic acid for biofilm formation, which disturbance affect the cell wall structure and drastically affect the extracellular matrix anchoring [36, 37]. Lipoteichoic acid (LTA) is a major component of the cell wall in Gram-positive bacteria, and the LTA synthase ( BC3765 ) is upregulated in 48- and 72-hour aged biofilms.…”
Section: Resultsmentioning
confidence: 99%
“…Both pathogenic bacteria showed alterations in the PG layer as a result of treatment with the antibiotic tunicamycin, which inhibits the WTA biosynthetic enzyme TagO 48 . Classical negative stain and sectioning TEM showed that the PG layer of L. monocytogenes and S. aureus appears thinner and rougher upon tunicamycin administration 47 . The micrographs from these studies show a striking resemblance with our data of the S. coelicolor sacculi treated with HF.…”
Section: Discussionmentioning
confidence: 97%
“…Our data further indicate that TAs play an essential role in the structural integrity of the cell wall by tethering the distinct lamellae of the cell wall to one another. The role of the TAs in the cell wall structure has been previously studied in the Gram-positive pathogens Staphylococcus aureus and Listeria " 10 monocytogenes 47 . Both pathogenic bacteria showed alterations in the PG layer as a result of treatment with the antibiotic tunicamycin, which inhibits the WTA biosynthetic enzyme TagO 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Because most staphylococcal phages require WTA as their receptor (Azam and Tanji 2019b), we sought to determine whether our SP phages also require WTA. To this end, we generated WTA-free Staphylococcus by inhibiting WTA synthesis in the cell using tunicamycin (Zhu et al 2018). ɸSA039, ɸSA012, and three SP phages (ɸDP001, ɸSP120, and ɸSP197) had no ability to infect WTA-free S. pseudintermedius and S. epidermidis (data not shown).…”
Section: Resultsmentioning
confidence: 99%